Peran Pengawas terhadap Profesionalisme Guru melalui in House Training (IHT) pada TK Islam Terpadu Ananda - Aisyah, Siti; Yusrianti, Susi; Siregar, Fauzan Ahmad (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
The primary responsibility of school supervisors in general is to supervise in the managerial and academic fields. The role of school administrators is critical in overcoming problems, particularly in increasing teacher professionalism and adapting to technological advances and changing times. Teacher professionalism refers to the necessary competencies, which include pedagogic competence, personal competence, professional competence, and social competence. In today's globalized world, school administrators are faced with roles that require more skills in terms of school construction. The following are the goals of this study: Describe the supervisory role of teacher professionalism at the Ananda Pante Raya Integrated Islamic Kindergarten in the Wih Pesam sub-district of the Bener Meriah district. 2) Describe how IHT was implemented at Ananda Integrated Islamic Kindergarten in the Wih Pesam. This is a qualitative study that takes a descriptive approach and employs case study analysis. The findings of the study are as follows: 1). School supervisors are capable of carrying out their roles effectively in Ananda Integrated Islamic Kindergarten, which includes the role of school supervisors as trainers, coaches, mentors, innovators, motivators, facilitators, and motivators. As the supervisor of the Ananda Integrated Islamic Kindergarten, he has been able to invest in improving teacher professionalism as a resource, coworker, and relation. 2) The Ananda Integrated Islamic Kindergarten's in-house training activities have an effect on changes in good character, changes in the social field, personal changes, pedagogical changes, and changes in professional competence. This in-house training activity was developed through discussions with school supervisors, principals, and teachers.